Limited Sampling Strategies for Estimating Intravenous and Oral Cyclosporine Area Under the Curve in Pediatric Hematopoietic Stem Cell Transplantation. Issue 2 (April 2015) - Sarem, Sarem; Nekka, Fahima; Barrière, Olivier; Bittencourt, Henrique; Duval, Michel; Teira, Pierre; Haddad, Elie; Théorêt, Yves; Lapeyraque, Anne-Laure; Litalien, Catherine
Abstract : Background: The optimal monitoring strategy for cyclosporine (CsA) in pediatric hematopoietic stem cell transplantation (HSCT) patients remains unclear. Although there is a growing interest in the use of the area under the concentration–time curve (AUC), measurement of AUC in clinical settings is often impractical. The objective of this study was to identify and validate limited sampling strategies (LSSs) for the prediction of CsA AUC after intravenous (IV) and oral (PO) administration in this population. Methods: Sixty-eight pediatric patients who underwent HSCT and received CsA were investigated. Twelve-hour pharmacokinetic profiles (n = 138) performed per standard of care were collected. Weighted multiple linear regression was used to investigate all possible LSSs consisting of 4 or less concentration–time points. Their predictive performance was evaluated by leave one out cross validation and external validation by measuring the root mean squared relative error (RMSE%) and the 95th percentile of the absolute relative error (AE%). Values less than 20% were considered clinically acceptable. Results: Nine LSSs (4 IV and 5 PO) convenient for clinical application proved to have clinically acceptable performance. Notably, LSS based on C0, C2, and C4 was found to be accurate for estimation of CsA exposure after both IV and PO administration with the 95th percentile of AE% of 19.7% and 17.5%, respectively. Conclusions: LSSs using 3 or 4 concentration–time points obtained within 4 hours postdose provide a convenient and reliable method to estimate CsA exposure in this population. These LSSs may facilitate future research aiming at better defining the relationship between AUC and clinical outcomes.